Pengaruh Model Pembelajaran Kooperatif Tipe DMR (Diskursus Multi Representasi) terhadap Hasil Belajar Matematika Siswa Kelas VII SMP Negeri 5 Mengkendek, Tana Toraja - Fortune, Dyhonest Pigeon; Djadir; Djam'an, Nurwati (Issues in Mathematics Education (IMED), 2018)
This research is a quasi experimental research which aims to know the influence of cooperative learning model type multi representative discourse towards mathematics learning achievement of 7th grade students of SMP Negeri 5 Mengkendek, Tana Toraja.The population is students of SMP Negeri 5 Mengkendek academic year2017/2018. Sampling technique is cluster method, in this case selected 2 class as experimental class and control class. Data collection is observation sheet of learning implementation and test of mathematics learning achievement. Data analysis used SPSS statistical data processing program. The result of descriptive statistical analysis shows: (1) learning implementation by using cooperative learning model type multi representative discoursein very good category (2) the implementation of learning by using conventional learning model in very good category, (3) mathematics learning achievement of two classin high category, whereas in the experimental class obtained average score 85.74 with standard deviation 8.49 from the ideal score 100 and in the control class obtained average score 80.13 with deviation 6.45 from ideal score 100. The result of inferential analysis shows the learning achievement of students used cooperative learning model type multi representative discourse is higher than the result of student used conventional learning model.